OLIGOCELLULA1/HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES15 Promotes Cell Proliferation With HISTONE DEACETYLASE9 and POWERDRESS During Leaf Development in Arabidopsis thaliana - Suzuki, Marina; Shinozuka, Nanae; Hirakata, Tomohiro; Nakata, Miyuki T.; Demura, Taku; Tsukaya, Hirokazu; Horiguchi, Gorou (Frontiers in Plant Science, 2018)
Organ size regulation is dependent on the precise spatial and temporal regulation of cell proliferation and cell expansion. A number of transcription factors have been identified that play a key role in the determination of aerial lateral organ size, but their functional relationship to various chromatin modifiers has not been well understood. To understand how leaf size is regulated, we previously isolated the oligocellula1 (oli1) mutant of Arabidopsis thaliana that develops smaller first leaves than the wild type mainly due to a reduction in the cell number. In this study, we further characterized oli1 leaf phenotypes and identified the OLI1 gene as well as interaction partners of OLI1. Detailed characterizations of leaf development suggested that the cell proliferation rate in oli1 leaf primordia is lower than that in the wild type. In addition, oli1 was associated with a slight delay of the progression from the juvenile to adult phases of leaf traits. A classical map-based approach demonstrated that OLI1 is identical to HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES15 (HOS15). HOS15/OLI1 encodes a homolog of human transducin β-like protein (TBL1). TBL1 forms a transcriptional repression complex with the histone deacetylase HDAC3 and either nuclear receptor co-repressor (N-CoR) or silencing mediator for retinoic acid and thyroid receptor (SMRT). We found that mutations in HISTONE DEACETYLASE9 (HDA9) and a SANT (switching-defective protein 3, adaptor 2, N-CoR, and transcription factor IIIB)-domain protein gene, POWERDRESS (PWR), showed a small-leaf phenotype similar to oli1. In addition, hda9 and pwr did not further enhance the oli1 small-leaf phenotype, suggesting that these three genes act in the same pathway. Yeast two-hybrid assays suggested physical interactions, wherein PWR probably bridges HOS15/OLI1 and HDA9. Earlier studies suggested the roles of HOS15, HDA9, and PWR in transcriptional repression. Consistently, transcriptome analyses showed several genes commonly upregulated in the three mutants. From these findings we propose a possibility that HOS15/OLI1, PWR, and HDA9 form an evolutionary conserved transcription repression complex that plays a positive role in the regulation of final leaf size.